Dakwah Digital dalam Pendidikan Islam: Implementasi Bimasoft dan Safe Exam sebagai Strategi Pencegahan Kecurangan dan Penanaman Nilai Amanah di SMA Al-Fityan Kubu Raya - Andhika Valentino; Tasya Tasya; Helmi Helmi; Wafiq Wafiq; Dede Dede; Reizaldi Rezaldi (J-MD Jurnal Manajemen Dakwah, 2025)
The rapid expansion of digital technology in Islamic education has created new challenges in maintaining academic integrity, particularly during computer-based examinations. This study addresses the issue of academic dishonesty in digital assessment settings and explores how technological tools can be aligned with Islamic values, especially the principle of amanah (trustworthiness). The purpose of this research is to analyze the implementation of Bimasoft and Safe Exam applications as an integrated strategy for preventing cheating while fostering amanah in students within an Islamic educational environment. Using a descriptive qualitative approach, data were collected through in-depth interviews with teachers, operators, and school management, complemented by documentation of exam procedures. The findings show that Bimasoft improves exam efficiency through streamlined question input, randomized items, and automated scoring, while Safe Exam effectively restricts access to external applications, thereby reducing opportunities for cheating. However, the success of these systems remains dependent on human factors, particularly the vigilance of exam proctors. The study implies that digital examinations can function not only as technical assessment tools but also as instruments of digital da’wah that reinforce moral discipline and accountability. The novelty of this research lies in its integration of technological exam systems with Islamic ethical formation, demonstrating how digital platforms can operationalize spiritual values in contemporary education.